2017
DOI: 10.1001/jamaoncol.2016.5478
|View full text |Cite
|
Sign up to set email alerts
|

The KRAS-Variant and Cetuximab Response in Head and Neck Squamous Cell Cancer

Abstract: Importance There is a significant need to find biomarkers of response to radiation and cetuximab in locally advanced head and neck squamous cell carcinoma (HNSCC), as well as biomarkers predicting altered immunity, thereby enabling personalized treatment. Objective To evaluate if the KRAS-variant, a germ-line mutation in a microRNA-binding site in KRAS, is a predictive biomarker of cetuximab response and altered immunity in the setting of radiation and cisplatin treatment. To evaluate the interaction of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 48 publications
0
40
0
Order By: Relevance
“…C225 in combination with EGFR not only blocked the secretion of TGF-and signal transduction but also decreased the expression of EGFR on the cell membrane surface (Liao and Carpenter, 2009). Clinically, C225 combined with radiotherapy showed a significant effect on head and neck squamous cell carcinoma and C225 combined with radiotherapy as a routine treatment on head and neck squamous cell carcinoma has been accepted by the majority of doctors (Sok et al, 2006;Pozzi et al, 2016;Suntharalingam et al, 2017 ;Weidhaas et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…C225 in combination with EGFR not only blocked the secretion of TGF-and signal transduction but also decreased the expression of EGFR on the cell membrane surface (Liao and Carpenter, 2009). Clinically, C225 combined with radiotherapy showed a significant effect on head and neck squamous cell carcinoma and C225 combined with radiotherapy as a routine treatment on head and neck squamous cell carcinoma has been accepted by the majority of doctors (Sok et al, 2006;Pozzi et al, 2016;Suntharalingam et al, 2017 ;Weidhaas et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Others have identified SNPs that may be associated with toxicity and/or outcome in cancer patients treated with EGFR-directed treatment [3,4,6,[17][18][19][20][21]. Lately, studies have suggested that activation of RAS signaling in the tumor is associated with response to cetuximab [28,29]. (C) Figure 2.…”
Section: Discussionmentioning
confidence: 99%
“…Notably the KRAS -variant germline and MAPK1 E322K mutation were highlighted in recent literature. Patients harboring a germline mutation in the micro-RNA binding site of KRAS have poorer overall survival [57]. Surprisingly, in a phase III trial in which cetuximab did not confer benefit when added to chemoradiation in unselected HNSCC patients [29], patients with the KRAS -variant (70 of 413 patients tested) had increased OS in the first two years following treatment with cetuximab (HR 0.19; 95% CI, 0.04–0.86; P = 0.03) [57].…”
Section: Insights From Genomic Researchmentioning
confidence: 99%
“…In KRAS -variant patients, TFG-β1 was found to be upregulated; this cytokine has been implicated in suppressing antitumor immunity through regulatory T-cell induction [58]. Authors of this study proposed that through ADCC and improved dendritic cell priming of cytotoxic T lymphocytes, cetuximab bolstered the antitumor immunity otherwise inhibited in KRAS -variant patients [57]. …”
Section: Insights From Genomic Researchmentioning
confidence: 99%